Physicochemical characterization and stability of chia oil microencapsulated with sodium caseinate and lactose by spray-drying - Ixtaina, Vanesa Yanet (2014)
Microencapsulation is an alternative to protect chia oil from the adverse influence of the environment, since this oil is susceptible to oxidation due to their high content of polyunsaturated fatty acids (PUFAs). The aim of this study was to investigate the influence of the operating conditions (homogenization pressure for emulsifying and spray-drying inlet/outlet temperatures) on the physicochemical properties of chia oil microencapsulated with sodium caseinate and lactose by spray-drying. Oil-in-water emulsions were prepared with 10 %wt/wt sodium caseinate, 10 %wt/wt lactose and 10 %wt/wt chia oil using a high pressure homogenizer at 400 and 600 bar. These emulsions were spray-dried at inlet/outlet temperatures of 135/70 °C and 170/90 °C. The microcapsules were approximately spherical in shape with some small pores and a polydisperse particle size distribution, recording moisture contents of 1.48–3.52 g/100 g (d.b.). The encapsulation efficiency was > 90% in all cases. The particle size distributions of parent and reconstituted emulsions displayed a unimodal distribution. The emulsion reconstituted of microcapsules obtained from emulsions at 400 bar presented a higher initial particle size (D [4,3] = 0.48–0.54 μm; D [3,2] = 0.31–0.33 μm) than those prepared at 600 bar (D [4,3] = 0.33–0.35 μm; D [3,2] = 0.24–0.25 μm). The dispersibility of microcapsules was assessed by measuring the change in droplet obscuration as a function of time. Physical stability of the different reconstituted emulsions was studied by recording the backscattering profiles (BS) as a function of the cell length and time. Regarding oxidative stability during storage, chia bulk oil showed higher peroxide values (PV) than microencapsulated oil during storage. The microcapsules obtained from emulsions at 600 bar showed higher PV than those at 400 bar. The results indicate that the microencapsulation process consisting of emulsification using high-pressure valve homogenizer and subsequent spray-drying is suitable for preparing sodium caseinate-lactose-based microcapsules containing chia oil.